Main Barriers in Reducing Microbial Load in Raw Vegetables Served on Brazilian School Menus - Sueny Andrade Batista; Emanuele Batistela dos Santos; Gabriel Teles Câmara; Ester Cardoso Paes Rose; Pedro Tourinho Dantas; Raquel Braz Assunção Botelho; Verônica Cortez Ginani (Hygiene)
This study assessed raw vegetable sanitizing in Brazilian schools and identified barriers to standards. This experimental and quantitative study was conducted in 12 school food services in the Federal District (Brazil) public primary education institutions. Microbiological analyses were conducted with vegetable samples (before and after sanitizing) and water used in the sanitization process, collected before the process. The Petrifilm®E. coli/Coliform Count Plates and COLIlert methods were used to evaluate vegetables and water samples, and a checklist of good practices was applied in each school food service to identify barriers to proper sanitization. Thirty-five samples of raw vegetables were offered to students, 32 samples of water, and 17 hygiene processes were evaluated. The results indicate that 76.5% (n = 13) of hygiene processes were considered unsatisfactory, with an average increase of 5.8 log CFU g−1 (DV = 7.4) in the initial microbial load in 47.1% (n = 8) of the evaluated processes; moreover, 33.3% (n = 6) of the samples exceeded the tolerable limit, with an average value above 1.5 × 103 CFU/g. Attention to food handler training and necessary organizational changes is essential to ensure safe food and promote healthy student eating habits, highlighting the importance of strengthening basic hygiene practices and following the parameters for sanitizing vegetables.